2007
DOI: 10.1016/j.jconrel.2007.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel distribution in poly(ethylene glycol)/poly(lactide-co-glycolic acid) blends and its release visualized by coherent anti-Stokes Raman scattering microscopy

Abstract: Mechanisms underlying the release of paclitaxel (PTX) from poly(ethylene glycol)/poly(lactic-coglycolic acid) (PEG/PLGA) blends were investigated by coherent anti-Stokes Raman scattering (CARS) microscopy. PLGA, PEG, and PTX were selectively imaged by using the resonant CARS signal from the CH 3 , CH 2 , and aromatic CH stretch vibrations, respectively. Phase segregation was observed in PLGA films containing 10 to 40 wt.% PEG in the absence of PTX loading. The PEG phase existed in the form of crystalline fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 30 publications
6
57
0
1
Order By: Relevance
“…37 Raw DPPE-PEG showed the presence of strong peaks at 19° and 23° 2Θ, a small peak at 21° 2Θ, and smaller broad peaks above 25° 2Θ. The peaks at 19°, 23°, and above 25° 2Θ are similar to previous results for PEG powder, 46 whereas the peak at 21° 2Θ corresponds to the presence of a phospholipid bilayer. Upon spray-drying, the peaks above 25° 2Θ disappeared, whereas the peaks at 19° and 23° 2Θ remained for all formulated particle systems.…”
Section: Powder X-ray Diffractionsupporting
confidence: 86%
“…37 Raw DPPE-PEG showed the presence of strong peaks at 19° and 23° 2Θ, a small peak at 21° 2Θ, and smaller broad peaks above 25° 2Θ. The peaks at 19°, 23°, and above 25° 2Θ are similar to previous results for PEG powder, 46 whereas the peak at 21° 2Θ corresponds to the presence of a phospholipid bilayer. Upon spray-drying, the peaks above 25° 2Θ disappeared, whereas the peaks at 19° and 23° 2Θ remained for all formulated particle systems.…”
Section: Powder X-ray Diffractionsupporting
confidence: 86%
“…[57][58][59][60] The preferential association of PCTX with PEG was observed by coherent anti-stokes Raman scattering microcopy by Kang et al, 61 and this association was validated by the disappearance of the sharp crystallization peaks of PEG under XRD in the presence of PCTX. 61 Here, the association between PCTX and PEG was qualified by the strong positive correlations between the parallel release of PCTX and PEG (Figure 8). This correlation also showed a dependence on the concentration of the PEG additives, particularly with PEG10k.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, Kang et al investigated the paclitaxel distribution in PLGA/PEG blends by selectively imaging the three components using coherent anti-Stokes Raman scattering (CARS) microscopy. 27 In the 9:1 and 8:2 PLGA/PEG films, they not only observed that paclitaxel preferentially partitioned into the PEG domains in the blends, but also found that the strong interactions between paclitaxel and PEG prevented the crystallization of PEG. Moreover, they observed a uniform mixing of paclitaxel in both PLGA and PEG in PLGA/PEG (7:3) films.…”
Section: Introductionmentioning
confidence: 98%